INTERPLAY AMONG CUSTOMER SATISFACTION (CARRYOVER), REPURCHASE INTENTION AND CUSTOMER LOYALTY: AN ANALYSIS THROUGH HIERARCHICAL LINEAR MODELING. - Dr. Pardeep Bawa Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper intends to explore the influence of Customer Satisfaction (Carryover [CSC] on repurchase intention (RI). To evaluate that, it is hypothesized that CSC influences RI that in turn goes on to influence customer loyalty (CL). Data were collected from 325 customers of 3 major modern retail chains in India. A mediation and moderation analysis was utilized along with hierarchical liner modeling to achieve these objectives. Results showed that a) CSC significantly influences RI and CL. b) RI mediates between CSC and CL and c) CSC moderates the relationship between RI and CL.